2007
DOI: 10.3758/bf03193105
|View full text |Cite
|
Sign up to set email alerts
|

Distractor effects during processing of words under load

Abstract: The perceptual load model of attention (Lavie, 1995) suggests that processing of irrelevant distractors depends on the extent to which a relevant task engages full perceptual capacity. Word recognition models suggest that letter perception is facilitated in words relative to nonwords. These models led us to hypothesize that increasing the number of letters would increase perceptual load more for nonwords than for words, and thus would be more likely to exhaust capacity and eliminate distractor processing for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Interestingly, different models of distractor inhibition predict different patterns of results. If distractor suppression and target enhancement are dependent on common neural mechanisms (e.g., Dalton, Lavie, & Spence, 2009;Brand-DʼAbrescia & Lavie, 2007;Lavie & De Fockert, 2005), then the same WME conditions that delay attention-related enhancement of a subsequent target would also delay attention-related suppression. Other models of distractor suppression, however, propose that it may proceed independently from target enhancement if target and distractor processing are dependent on different neural systems (e.g., Park, Kim, & Chun, 2007;Kim, Kim, & Chun, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, different models of distractor inhibition predict different patterns of results. If distractor suppression and target enhancement are dependent on common neural mechanisms (e.g., Dalton, Lavie, & Spence, 2009;Brand-DʼAbrescia & Lavie, 2007;Lavie & De Fockert, 2005), then the same WME conditions that delay attention-related enhancement of a subsequent target would also delay attention-related suppression. Other models of distractor suppression, however, propose that it may proceed independently from target enhancement if target and distractor processing are dependent on different neural systems (e.g., Park, Kim, & Chun, 2007;Kim, Kim, & Chun, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the third group (see Fig. 1C), PL is increased by making it more difficult to discriminate among the possible targets (Bahrami, Carmel, Walsh, Rees, & Lavie, 2008;Brand-D'Abrescia & Lavie, 2007;Cartwright-Finch & Lavie, 2007;Couperus, 2001;Handy & Mangun, 2000;Taya, Adams, Graf, & Lavie, 2009). In the fourth group (see Fig.…”
Section: Perceptual Loadmentioning
confidence: 99%
“…Although evidence from numerous studies provides support for perceptual load theory (e.g., Bahrami, Carmel, Walsh, Rees, & Lavie, 2008;Brand-D'Abrescia & Lavie, 2007;Cartwright-Finch & Lavie 2007;Forster & Lavie, 2007;Lavie, 1995Lavie, , 2006Lavie & de Fockert, 2003;Lavie & Fox, 2000;Lavie & Robertson, 2001;Lavie et al, 2004;Muggleton, Lamb, Walsh, & Lavie, 2008), reported data are inconsistent with predictions of this theory. Using a name classification task, Lavie et al investigated the effect of perceptual load (set size) on the level of interference from a face distractor.…”
Section: Introductionmentioning
confidence: 96%